Functional donor site morbidity longer than one year after fibula free flap: A prospective biomechanical analysis. Issue 4 (26th July 2017) - Rendenbach, Carsten; Rashad, Ashkan; Hansen, Lara; Kohlmeier, Carsten; Dyck, Moritz L.; Suling, Anna; Assaf, Alexandre T.; Amling, Michael; Heiland, Max; Wikner, Johannes; Riecke, Bjoern; Kreutzer, Kilian
Abstract: Objectives: The fibula free flap is the workhorse procedure for osseous reconstruction. The objective of this study was to investigate long‐term functional outcomes of the harvesting site. Patients and Methods: About 19 patients (10 male, 9 female, mean age 58.1 years) were available for the long‐term analysis 13–51 months after surgery. Jumping mechanography and balance testing on a ground force reaction plate (Leonardo Mechanograph GFRP) were performed before and surgery. The Esslinger Fitness Index (EFI, maximum peak power in W/kg normalized for age and gender) was considered as primary endpoint. Secondary outcomes were maximum force, range of motion in the ankle joint, sensory limitations, the American Orthopedic Foot and Ankle Society Score (AOFAS‐Score), and subjective perceptions. Results: We found no significant difference between pre‐ and postoperative EFI (70.4% versus 66.0%, P  = 0.07) and body sway (1.72 cm 2 versus 2.60 cm 2, P  = 0.093). The AOFAS‐Score was reduced by 8.8 points (99.1 points versus 90.3 points, P  < 0.001). Dorsal extenstion (31.6° versus 24.1°, P  < 0.001) and flexion (32.3 versus 25.6° flexion, P  = 0.011) were significantly reduced and 6 patients had chronic pain. Conclusions: Reduced peak power and balance ability seem to be reversible short‐term effects after fibula harvesting. We recommend preoperative patient education and standardized protocols for physiotherapy.